2017
DOI: 10.1038/s41598-017-04946-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel oestrogen receptor β-selective ligand reduces obesity and depressive-like behaviour in ovariectomized mice

Abstract: Hormonal changes due to menopause can cause various health problems including weight gain and depressive symptoms. Multiple lines of evidence indicate that oestrogen receptors (ERs) play a major role in postmenopausal obesity and depression. However, little is known regarding the ER subtype-specific effects on obesity and depressive symptoms. To delineate potential effects of ERβ activation in postmenopausal women, we investigated the effects of a novel oestrogen receptor β-selective ligand (C-1) in ovariectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…In the ovariectomized animals fed with the control diet, we found no significant effects on the depressive-like behaviors measured in the FST. While these results agree with previous reports in rodents utilizing the same behavioral paradigm 12,1921 , other studies have found ovariectomy to induce depressive-like behaviors 11,17,18 . These contradictory fiings may be attributed to methodological discrepancies among these studies.…”
Section: Discussionsupporting
confidence: 93%
“…In the ovariectomized animals fed with the control diet, we found no significant effects on the depressive-like behaviors measured in the FST. While these results agree with previous reports in rodents utilizing the same behavioral paradigm 12,1921 , other studies have found ovariectomy to induce depressive-like behaviors 11,17,18 . These contradictory fiings may be attributed to methodological discrepancies among these studies.…”
Section: Discussionsupporting
confidence: 93%
“…The inhibitory effect of estradiol on food intake has been previously established ( Blaustein and Wade, 1976 ; Eckel, 2004 ). This anorexic effect of estrogen is further supported by the prevention of weight loss in ovariectomized animals ( Sasayama et al, 2017 ). A significantly reduced BW gain observed in the E 2 L1000 treatment group relative to TV group in our study could be partly due to this anorexic effect of E 2 .…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, recent reports have demonstrated that female mice lacking ERβ leads to dysregulation of brain-derived neurotrophic factor and serotonin signaling and decrease synaptic plasticity in the HPC, which could predispose the brain to a state of depression ( Chhibber et al, 2017 ). Likewise, ERβ-selective ligand reduces depressive-like behavior in ovariectomized mice ( Sasayama et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%